Data Analytics for Cardiotocography Data Using Principal Component Analysis - K, Pratuisha; Rao .D, Rajeswara; V.R.Murthy, J (International Journal of Engineering and Technology, 2018)
With growing congenital anamelies in recent years detection of heart problems in fetus has become critical. Cardiotocography test assists doctors in such dignosis followed by cure. Here analytics of cardiotocography data is presented in details.Understanding ,cleaning and preprocessing the data is one of the the foremost part for any researcher,In this work data is cleaned,preprocessed,normalized, Also the attributes are selected by using the Chi-square test. Colinearity problem is addressed using Principle component analysis.Such analytics and prepro-cessing will help in machine learning or allied models for predict-ing precise diagnosis at an early stage